Towards a Marine Spatial Plan for the Westfjords of Iceland - Sullivan, Abby (2011)
Verkefnið er unnið við Háskólasetur Vestfjarða Marine Spatial Planning (MSP) is widely recognized as being a key step to achieving ecosystem-based ocean and coastal management. It is a process that borrows tools from terrestrial planning, but that must also be adapted to address the unique challenges and qualities of the marine environment. It involves gathering spatial information in order to better visualize and understand the marine environment and to better inform management decisions that plan for the future. Recent interest sparked MSP initiatives around the world, most notably in Europe. Iceland, a country that has always depended on the sea for survival and which today still relies heavily on living marine resources, lacks an integrated management framework. To investigate which methods of MSP would be best suited for the Westfjords, this paper reviewed the current literature, compared MSP around the world in case studies, and trialled some of these methods in a small pilot area in Isafjarðardjúp (a large fjords system in the Westfjords). The results suggest that current conflicts on the water usually involve the fishing and aquaculture sector and that increased conflict in the future is expected as new technologies emerge (such as the wet renewables sector). It was established during the project that job creation, sustainable development and increasing the population are key values and objectives in the region. Information was gathered from interviews with local experts and GIS was then used to create maps to capture their knowledge on spatial use. Methods were then recommended to continue the MSP process in the Westfjords. In conclusion, MSP provides potential benefits and opportunities for reduced conflict and sustainable development through a better-informed and more efficient management regime in the Westfjords.